Vaccine-Based Immunotherapy for Metastatic Colorectal Cancer: A Systematic Review - Amelia, Sesa; Mathlubaa, Asya; Amly, Harzalina Zilfi; Jacobs, Christin Yosefin; Halim, Kurnia; Heriawan, Timotius Ivan; Guantoro, Vincent; Putri, Hesti Andika (Medicinus, 2025)
Background: Metastatic colorectal cancer (mCRC) remains a therapeutic challenge, particularly in microsatellite stable (MSS) tumors, which are largely unresponsive to current immunotherapy approaches. Vaccine-based immunotherapy offers a strategy to elicit tumor-specific immune responses in these immunologically “cold” tumors. However, clinical results have been mixed, and the efficacy and safety of cancer vaccines in mCRC remain to be clarified. Methods: A systematic review and meta-analysis were conducted in accordance with PRISMA 2020 guidelines. Randomized controlled trials (RCTs) evaluating vaccine-based immunotherapy in mCRC were identified from PubMed, EMBASE, and Scopus as of May 2, 2025. Eligible studies included human subjects with mCRC receiving vaccine therapy with or without additional treatments, compared to standard or placebo regimens. The primary outcomes were overall survival (OS) and progression-free survival (PFS); safety was assessed by the incidence of grade ≥3 treatment-related adverse events. Result: Five RCTs comprising 804 patients met inclusion criteria. Pooled analysis showed a trend toward improved OS with vaccine-based immunotherapy (HR 0.81; 95% CI, 0.65–1.00; p = 0.05; I² = 0%), and a modest, non-significant improvement in PFS (HR 0.80; 95% CI, 0.62–1.05; p = 0.07; I² = 0%). The incidence of severe adverse events was lower with vaccine-based therapies (RR 0.31; 95% CI, 0.02–6.09; p = 0.23; I² = 90%). Conclusions: Vaccine-based immunotherapy in mCRC demonstrates potential clinical benefit, particularly in prolonging survival with a favorable safety profile. Further biomarker-driven studies are needed to optimize patient selection and therapeutic combinations.